Rapid Bioassay for Detection of Thyroid-Stimulating Antibodies Using Cyclic Adenosine Monophosphate-Gated Calcium Channel and Aequorin - Araki, Naohiro (Eur Thyroid J, 2015)
BACKGROUND: Thyroid-stimulating antibodies (TSAb) are known to be responsible for hyperthyroidism in Graves' disease (GD). The conventional methods to measure TSAb depend on cell-based assays that require cumbersome procedures and a sterilized tissue culture technique. The aim of the present study was to develop a ready-to-use cell-based assay for measuring TSAb activity without requiring sterilized conditions. METHODS: We developed a new assay kit using a frozen Chinese hamster ovary cell line expressing the thyroid-stimulating hormone receptor, cyclic adenosine monophosphate (cAMP)-gated calcium channel and aequorin, tentatively named the aequorin TSAb assay. Activated stimulatory G-protein-coupled adenylate cyclase increases intracellular cAMP, which then binds to the cyclic nucleotide-gated calcium channel. Activation of this channel allows Ca(2+) to enter the cell, and the influx of Ca(2+) can be measured with aequorin, which is quantified by a luminometer. Results can be obtained in only 4 h without sterilized conditions. TSAb activities were expressed by international units using the NIBSC 08/204 standard. RESULTS: Positive results of aequorin TSAb were obtained in 197 of 199 (98.9%) of untreated patients with GD. Only 1 of 42 (2.3%) patients with painless thyroiditis had a weakly positive aequorin TSAb. All 45 patients with subacute thyroiditis and 185 normal subjects showed negative aequorin TSAb. As for chronic thyroiditis, all 52 euthyroid patients showed negative aequorin TSAb, but 8 of 50 (16.0%) hypothyroid patients had a positive reaction. However, these positive reactions were not induced by serum thyroid-stimulating hormone (TSH) and were thought to be induced by the stimulating activity of anti-TSH receptor immunoglobulins. Conventional porcine TSAb and Elecsys thyroid-stimulating hormone receptor antibodies were positive in 69.3 and 95.5% of GD, respectively. CONCLUSION: The aequorin TSAb assay was positive in 98.9% of GD and was more sensitive than the conventional assay. This assay can be conducted in only 4 h without sterilized conditions and is practically useful in general clinical laboratories.